Gender Gap in Scientific Publications on COVID-19 in Italy During the First Wave of the Pandemic: An Observational Study - Mazzalai, Elena; Turatto, Federica; De Vito, Corrado (Frontiers in Public Health, 2022)
Background Worldwide, concerns rise on how COVID-19 pandemic impacted heavily on women, even on those belonging to the scientific community. The Italian scientific production regarding the COVID-19 throughout the first months of the health emergency could help to understand the heft of female researchers in this unique period. Objectives This study aims to investigate the gender gap in the scientific production on COVID-19 in Italy during the first months of the pandemic. Methods A systematic search of the literature was conducted and, for each included study, first and last author's gender, type of study, number of co-authors, type of affiliation, journal's Impact Factor (IF) and specialization were extracted. Descriptive and univariate analyses were performed. Results 22.2% of the articles were signed by a woman as first author, 18.1% as last authors. Female authorship was less frequent than male authorship regardless of the type of study, number of co-authors, type of affiliation and field of specialization. Conclusion This analysis reveal a low prevalence of studies with a female first or last author and suggests that the low share of female authors publishing on COVID-19 during the considered timespan is a transversal issue throughout the Italian medical field.